Rethinking National Security in the Context of Nepal - Pandey, Muskan; Jha, Gunjan (Unity Journal, 2023)
This paper explores discourses of rethinking national security and the modern security challenges of Nepal, especially targeting the factors of both comprehensive and human security. The existing literature on Nepal has discussed the issues of threats such as fraud, cyber-crime, corruption, transnational organized crime, such as, illegal migration, identity politics raised by ethnic and religious groups, transit hub of narcotics, political disputes, economic downturns etc., and suggests ways of addressing those threats in both policies and implications. Security practices in Nepal sustains a gap in addressing non-traditional security mechanisms where the basic issues of the security dilemma, socio-cultural cohesion, political strength, diplomatic support, and military readiness are widely overlooked. In such a context, this paper explores the undergoing modern security challenges in Nepal based on a holistic approach. The critical constructivism perspective has been applied to rethink different dimensions of national security. This paper raises pertinent questions for strategic intervention in the contemporary context considering Nepal’s geostrategic importance, diplomatic presence, and national interest. The conclusion of the paper portrays the ways of ensuring national security which eventually helps security professional researchers and scholars.